2019
DOI: 10.22146/ijc.40891
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Reduction Behavior of Zirconia Doped to Nickel at Different Temperature in Carbon Monoxide Atmosphere

Abstract: The reduction behavior of nickel oxide (NiO) and zirconia (Zr) doped NiO (Zr/NiO) was investigated using temperature programmed reduction (TPR) using carbon monoxide (CO) as a reductant and then characterized using X-ray diffraction (XRD), nitrogen absorption isotherm using BET technique and FESEM-EDX. The reduction characteristics of NiO to Ni were examined up to temperature 700 °C and continued with isothermal reduction by 40 vol. % CO in nitrogen. The studies show that the TPR profile of doped NiO slightly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…However, the addition of zirconia would delay the reduction progress of MoO3 catalyst which was confirmed by detection of the remaining intermediate phase Mo4O11 in XRD diffractogram as compared to pure MoO3 catalyst. According the Gibbs, free energy changed the combination of MoO3 with ZrO2 and was able to increase the reduction temperature due to zirconia oxide difficulty to reduce [17]. Referring to the characterisation in XRD analysis, it confirmed that MoO3 catalyst can be reduced to MoO2 phase in CO atmosphere by involving two reduction stages, namely Mo 6+ → Mo 5+ and Mo 5+ → Mo 4+ [8].…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…However, the addition of zirconia would delay the reduction progress of MoO3 catalyst which was confirmed by detection of the remaining intermediate phase Mo4O11 in XRD diffractogram as compared to pure MoO3 catalyst. According the Gibbs, free energy changed the combination of MoO3 with ZrO2 and was able to increase the reduction temperature due to zirconia oxide difficulty to reduce [17]. Referring to the characterisation in XRD analysis, it confirmed that MoO3 catalyst can be reduced to MoO2 phase in CO atmosphere by involving two reduction stages, namely Mo 6+ → Mo 5+ and Mo 5+ → Mo 4+ [8].…”
Section: Resultsmentioning
confidence: 81%
“…This result was contrary with the desirable properties in zirconia addition for doping to enhance the reduction process. It suggested that there were some changes in the solid surface properties that particularly interrupted the reduction process [17]. It may due to the stable structure of alloy ZrMo2O8 (JCPDS 38-1466), which promoted a strong modification to the behaviour of the catalyst.…”
Section: Resultsmentioning
confidence: 99%